2000
DOI: 10.1105/tpc.12.9.1591
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function of a Rice brassinosteroid insensitive1 Homolog Prevents Internode Elongation and Bending of the Lamina Joint

Abstract: Brassinosteroids (BRs) are plant growth-promoting natural products required for plant growth and development. Physiological studies have demonstrated that exogenous BR, alone or in combination with auxin, enhance bending of the lamina joint of rice. However, little is known about the function of endogenous BR in rice or other grass species. We report here the phenotypical and molecular characterization of a rice dwarf mutant, d61 , that is less sensitive to BR compared to the wild type. We cloned a rice gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
688
3
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 658 publications
(717 citation statements)
references
References 39 publications
25
688
3
1
Order By: Relevance
“…Since d61-1 mutant is well-documented as a rice BRs insensitive mutant by Yamamuro et al [16], it was used as a positive control in root elongation inhibition assay. Our data clearly showed that d1 mutant was less sensitive to 24-EBL compared to wild-type plants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since d61-1 mutant is well-documented as a rice BRs insensitive mutant by Yamamuro et al [16], it was used as a positive control in root elongation inhibition assay. Our data clearly showed that d1 mutant was less sensitive to 24-EBL compared to wild-type plants.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of BR, the coleoptile of wild-type plants elongated more than that in the absence of BR; even the foliage leaves cannot break out of the coleoptile at high concentrations of BR in light [16]. These results suggested that BR is involved in the process of coleoptile elongation, and the extent of elongation can be considered reflect sensitivity to BR, since the length of elongation increased with increasing BR concentration.…”
Section: Coleoptile Elongation Response Of D1 Mutant To 24-epiblmentioning
confidence: 92%
See 3 more Smart Citations